Remote Speaking Tasks: Amplifying Understanding, Proficiency, and Confidence in English Learners - Tauchid, Ahmad; Widya Putri, Nanin Verina; Suwandi, Edi (ETERNAL (English Teaching Journal), 2024)
The increasing prevalence of technology has brought about a shift in teaching methods, notably with the rise of remote speaking tasks, utilizing digital platforms to enrich language learning experiences for English learners. In the context of language education, proficiency in English is increasingly recognized as a vital skill for academic, professional, and social success in today's interconnected world. Previous researchers have extensively explored various aspects of language learning, with a predominant focus on conventional classroom-based activities. However, there has been limited investigation into the potential benefits of remote speaking tasks specifically in enhancing understanding, proficiency, and confidence among English learners. The purpose of this study is to investigate the impact of remote speaking tasks on English learners' understanding, proficiency, and confidence. The study used open-ended surveys with 19 English students at Universitas Nahdlatul Ulama Sunan Giri, employing NVivo 12 to examine attitudes towards remote speaking tasks and achieving data saturation with this sample size. The findings emphasize the transformative impact of integrating remote speaking tasks and video creation in language learning, highlighting their significant benefits in enhancing comprehension, retention, critical skills, and English proficiency. The practical implications underscore the need for educators to adapt instructional methods by designing engaging activities, such as collaborative projects and creative language assignments, using platforms like VoiceThread and TikTok. These specific actions for educators aim to foster active learning, enhance students' speaking skills, confidence, adaptability, and fluency in real-life situations, while also developing essential 21st-century skills for academic and professional success.